(untitled) (Marketing Journal, 2025)
This article explores the pivotal role and profound importance of structural changes within the economy, which refer to fundamental shifts in the composition of economic sectors, production methods, and resource allocation. In the context of modern economi c development, structural transformations —such as the transition from agrarian to industrial and then to service -oriented economies —serve as key drivers of sustainable growth, innovation, and competitiveness. The paper analyzes the theoretical foundations of structural changes, drawing on classical and contemporary economic theories, including those of Joseph Schumpeter and the endogenous growth models. It examines real -world examples from developing and developed economies, highlighting how timely structur al reforms can mitigate economic imbalances, enhance productivity, and foster inclusive development. Furthermore, the article discusses challenges such as technological disruptions, globalization pressures, and policy implementation hurdles, while proposin g strategies for effective management of these changes. Ultimately, the study underscores that structural changes are not merely adaptive responses but essential mechanisms for long -term economic resilience and prosperity in an increasingly interconnected world.